Peningkatan Kesadaran Lingkungan dan Kesehatan Masyarakat Desa Somongari melalui Edukasi Dampak Pupuk dan Pestisida Anorganik - Purwanti Pratiwi Purbosari; Hadi Sasongko; Zuchrotus Salamah; Nurul Putrie Utami (Institut Pertanian Bogor, 2021)
Somongari Village, located in Purworejo District, Central Java Province, is well-known as a producer of durian and mangosteen fruits. The income of Somongari Villagers depends on this commodity, however because of durian and mangosteen can only be harvested during a specific season, the villager plans to build vegetable houses for their daily needs. Based on the data obtained through Forum Group Discussion (FGD) with representatives of the villager and farmer group, the villager had not used organic fertilizers and pesticides. The practicality and fast yield of inorganic fertilizers and pesticides are the reasons villagers use them more. In contrast, the application of inorganic fertilizers and pesticides can hurt the environment and human health. Therefore, education was carried out for the Somongari villagers to increase the knowledge and awareness of environmental sustainability and health, primarily due to inorganic fertilizer and pesticide impact. The method used in this event was include preparation (coordination and problem identification through FGD), implementation (delivery of material), evaluation, and follow-up plans. After this activity, public knowledge of the impact of inorganic fertilizers and pesticides has increased. It can be seen from the pretest and post-test scores, respectively, before and after the material's presentation. In addition, the success of this program can also be seen from the awareness of the villager to make follow-up plans related to the production of organic fertilizers and pesticides.